Imitation watermelon sheet jam made from watermelon albedo with natural coloring from roselle petals (Hibiscus sabdariffa L) and sappan wood (Caesalpinia sappan L) - Lestari, Oke Anandika; Dewi, Yohana Sutiknyawati Kusuma; Nabilah, Uray Ulfah; Hasbullah, Hasbullah; Ifwarisan Defri (Journal of Health and Nutrition Research, 2025)
The sheet jam was developed by reflecting on the practicality of sheet cheese. Sheet jam can be formed with the presence of hydrocolloids. Pectin is a hydrocolloid that is naturally contained in watermelon albedo. However, the use of watermelon albedo in making imitation watermelon sheet jam requires coloring and sweeteners. This study aims to obtain the physicochemical and sensory characteristics of imitation watermelon sheet jam using watermelon albedo with natural coloring and sweetener formulations. The treatments used were two types of natural dyes (roselle and sappanwood) and sweetener formulations (fructose, honey, sucrose). The psychochemical characteristics tested were water content, reducing sugar content, total acid, and color. Sensory characteristics were tested descriptively and hedonic quality. Data analysis has been carried out using OPLS-DA, followed by OPLS, and Pearson’s correlation (by SIMCA 14.1). The findings showed that the main physicochemical and sensory characteristics of imitation watermelon sheet jam were herbal aroma, fruit aroma, chewy texture, sweetness, reducing sugar, Hue (red/yellow), rollability, and overall preference. The characteristics that determine the level of preference for imitation watermelon sheet jam were rollability, sweetness, shiny appearance, and chewy taste. The sweet taste characteristic (r -0.92582) has a negative correlation with the level of preference. The presence of a doctoring agent (fructose or honey) prevents crystallization in sheet jam, which is positively correlated with preference. Coloring with Roselle and sappanwood can replace the use of watermelon flesh and can be further studied in relation to the functional characteristics that may be provided.